2001
DOI: 10.1002/jgm.223
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus type 5 uptake by lung adenocarcinoma cells in culture correlates with Ad5 fibre binding is mediated by ?v?1 integrin and can be modulated by changes in ?1 integrin function

Abstract: Our studies demonstrate that the Ad5 fibre-knob domain interaction with CAR represents a major determinant of Ad5-mediated gene transfer to lung-derived adenocarcinoma cells in culture. The finding that integrin alpha(v)beta1 is involved in Ad5 infection has implications for the use of recombinant Ad5 vectors for cancer gene therapy, since alpha(v)beta1 is expressed at high levels and acts as an alternative vitronectin receptor in many epithelial and some melanoma tumours which express no alpha(v)beta3 and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 34 publications
2
30
0
1
Order By: Relevance
“…This process requires the presence of both primary and secondary receptors for the Ad5 virion (i.e., CAR and a 3 b V or a 5 b V integrins) on the cell surface at levels sufficient to allow binding by the vector. 46,47 As most of the clinical tumor cell isolates are heterogeneous, we have tested all our cell lines for susceptibility to Ad5 vector infection by titrating the replication competent rcAd/ CMV-GFP vector on each of the cell lines (Fig 4). The ability of rcAd/CMV-GFP to replicate in all human cell lines allows for an easy detection of transduced cells, since vector genome amplification boosts GFP expression levels many fold.…”
Section: Bt Cell Lines Are Efficiently Transduced By Ad5-based Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process requires the presence of both primary and secondary receptors for the Ad5 virion (i.e., CAR and a 3 b V or a 5 b V integrins) on the cell surface at levels sufficient to allow binding by the vector. 46,47 As most of the clinical tumor cell isolates are heterogeneous, we have tested all our cell lines for susceptibility to Ad5 vector infection by titrating the replication competent rcAd/ CMV-GFP vector on each of the cell lines (Fig 4). The ability of rcAd/CMV-GFP to replicate in all human cell lines allows for an easy detection of transduced cells, since vector genome amplification boosts GFP expression levels many fold.…”
Section: Bt Cell Lines Are Efficiently Transduced By Ad5-based Vectorsmentioning
confidence: 99%
“…46,47 We determined cell surface levels of FasR and DR4 and DR5 (functional TRAIL receptors) for each cell line using flow cytometry (Fig 5). The majority of cell lines had levels of FasR comparable to or greater than those of HeLa.…”
Section: Death Ligand Gene Therapy Of Brain Tumor Cells S Rubinchik Ementioning
confidence: 99%
“…A strong correlation between the expression of CAR on the cell surface and the level of transgene expression in photochemically treated cells was observed, suggesting that the absolute level of virus binding to the cell surface determines the level of transduction in photochemically treated cells, as reported by other groups for conventional adenoviral infection. [18][19][20] Blocking CAR with recombinant Ad5 fiber-knob resulted in a complete inhibition of gene expression, both in conventionally infected and in photochemically treated cells. These results strengthen the assumption that attachment to the cell surface is a key event for PCI-mediated transduction and suggest further that nonreceptor-mediated uptake pathways are not involved in the photochemical transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Using the RmcB anti-CAR monoclonal antibody, 13 we found that the cell lines used in this study expressed different levels of CAR ( Table 1) Fig 1b), as previously reported by other groups. [18][19][20] The relationship between the expression of CAR and the percentage of b-galactosidasepositive cells in photochemically treated cells showed an even better linear correlation (P ¼ .002 , Fig 1b), suggesting that virus binding to the cell surface is of fundamental importance also for photochemical transduction.…”
Section: Influence Of Car On Photochemical Transductionmentioning
confidence: 99%
“…The human non-small cell carcinoma cell line, A549, is widely used to study the role of integrins in normal and pathophysiological processes (36)(37)(38)(39)(40)(41)(42)(43)(44). We validated the presence of ABI in this tumor model by Western blot and immunohistochemistry (IHC).…”
Section: A549 Tumor Cells Express Abimentioning
confidence: 99%